2021
DOI: 10.1016/j.cegh.2021.100747
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of seroprevalence of novel coronavirus disease (COVID-19) using preserved serum at an outpatient setting in Kobe, Japan: A cross-sectional study

Abstract: Objectives Coronavirus disease 2019 (COVID-19) pandemic caused by SARS-CoV-2 has been affecting many people on earth and our society. Japan is known to have relatively smaller number of its infections as well as deaths among developed nations. However, accurate prevalence of COVID-19 in Japan remains unknown. Therefore, we conducted a cross-sectional study to estimate seroprevalence of SARS-CoV-2 infection. Methods We conducted a cross-sectional serologic testing for SA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 10 publications
0
23
1
Order By: Relevance
“…Since the emergence of SARS-CoV-2, assessing and understanding the kinetics and protective role of the human immune response against this virus, has been of a high priority and relevance [ 4 ]. For this purpose, different investigations have conducted several seroepidemiological surveys worldwide to measure the seroprevalence of antibodies against SARS-CoV-2 [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. These studies have demonstrated the importance of the humoral immune response for the elimination of viral infection, and the important role of understanding the dynamics of antibodies against SARS-CoV-2, which help not only in assessing immunological levels and predicting potential immune protection, but also in the development of vaccine and immune therapy strategies [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the emergence of SARS-CoV-2, assessing and understanding the kinetics and protective role of the human immune response against this virus, has been of a high priority and relevance [ 4 ]. For this purpose, different investigations have conducted several seroepidemiological surveys worldwide to measure the seroprevalence of antibodies against SARS-CoV-2 [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. These studies have demonstrated the importance of the humoral immune response for the elimination of viral infection, and the important role of understanding the dynamics of antibodies against SARS-CoV-2, which help not only in assessing immunological levels and predicting potential immune protection, but also in the development of vaccine and immune therapy strategies [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Positive detection of SARS-CoV-2 RNA in nasopharyngeal swab samples, sputum samples or bronchoalveolar lavage samples by reverse transcriptase polymerase chain reaction (RT–PCR) has been used to confirm SARS-CoV-2 infection. Recently, positive detection of IgM and IgG antibodies specific to SARS-CoV-2 has also been recognized as deterministic evidence for confirmed SARS-CoV-2 infection [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of dialysis patients in the United States, 8~9% of the population was estimated to be infected, but less than 2% were confirmed cases [ 14 ]. In a cross-sectional study of outpatients in Kobe, Japan, seroprevalence was 396 to 858 times higher than the number of confirmed cases [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, despite high urbanization and population density, there were relatively few missed cases. Kobe, Japan had an estimated seroprevalence of 2.7%, while Santa Clara County had 1.2% [ 13 , 15 ]. However, highly urbanized New York state showed an average of 12.5% positives, and numbers increased in densely populated areas such as New York City, with 20.2% [ 17 ].…”
Section: Discussionmentioning
confidence: 99%